Determinan Penyerapan Tenaga Kerja Sektor Pertanian - marthen ai nahumury; Ali Ali Mustofa (Faculty Of Economics and Business, Musamus University, 2024)
ABSTRACT This research aims to determine and analyze the agricultural sector's Gross Regional Domestic Product (GRDP), Farmer Exchange Rate (NTP), and Investment in labor absorption in Papua Province from 2010 to 2022. The type of data used is secondary data taken from 2010 to 2022. Data was analyzed using quantitative methods, and the technique used was multiple linear regression analysis with the help of SPSS. 21. The influence of GRDP in the agricultural sector on labor absorption based on the analysis results shows that the hypothesis is accepted where t count > t table, the significant value < probability 0.05, and the coefficient value is -0.19. Thus, GRDP in the agricultural sector has a negative and significant effect on absorption labor, Farmer Exchange Rate based on the results of the analysis, it can be seen that the hypothesis is accepted, where t count>t table 8hthus the Farmer Exchange Rate has a negative and significant effect on sector labor absorption agriculture. Agricultural Sector Investment has a positive and insignificant impact, while the regression coefficient value is 0.010. This means that if investment in the agricultural sector increases by 1 percent, employment in the agricultural sector in Papua Province will increase by 0.010 or 1 percent. Simultaneously, GRDP in the agricultural sector, Farmer Exchange Rate (NTP), and Investment influence employment in the agricultural sector in Papua Province. Keywords: Gross Regional Domestic Product (GRDP) in the agricultural sector, Farmer Exchange Rate (NTP), Investment and Labor Absorption.